2020
DOI: 10.1038/s41419-020-2227-4
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer activity of dietary xanthone α-mangostin against hepatocellular carcinoma by inhibition of STAT3 signaling via stabilization of SHP1

Abstract: Hepatocellular carcinoma (HCC) is one of the most lethal human cancers worldwide. The dietary xanthone αmangostin (α-MGT) exhibits potent anti-tumor effects in vitro and in vivo. However, the anti-HCC effects of α-MGT and their underlying mechanisms are still vague. Aberrant activation of signal transducer and activator of transcription 3 (STAT3) is involved in the progression of HCC. We therefore investigated whether α-MGT inhibited the activation of STAT3 and thereby exhibits its anti-HCC effects. In this st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 49 publications
(76 reference statements)
1
14
0
Order By: Relevance
“…33 Studies concluded that doses closer to CC50 accentuated pro-oxidant effects. 33,34 In contrast, the study by Hafeez et al showed a dose-dependent decrease in intracellular and extracellular SOR with continued induction of apoptosis in pancreatic cancer cells. The study concluded that the ability to modulate ROS by alpha mangostin depends on the type of cell studied.…”
Section: Discussionmentioning
confidence: 87%
“…33 Studies concluded that doses closer to CC50 accentuated pro-oxidant effects. 33,34 In contrast, the study by Hafeez et al showed a dose-dependent decrease in intracellular and extracellular SOR with continued induction of apoptosis in pancreatic cancer cells. The study concluded that the ability to modulate ROS by alpha mangostin depends on the type of cell studied.…”
Section: Discussionmentioning
confidence: 87%
“…31 Moreover, α-M could inactivate STAT3, thus exhibiting its antitumor effects on hepatocellular carcinoma. 32 Previously, EBI3 was shown to activate STAT3, thus inducing the proliferation of IL-6-dependent mouse plasmacytoma cells. 33 Here, we reported that the…”
Section: Discussionmentioning
confidence: 99%
“…Mangosteen xanthones, especially MAG and GA, have been proven to display significant chemo-preventive and anticancer properties against numerous tumor types [12,[15][16][17][25][26][27]. Moreover, chemical modification of the xanthone structure is believed to further increase the anticancer properties, as described in [28,29].…”
Section: Discussionmentioning
confidence: 99%